Anti‐addiction drug ibogaine inhibits hERG channels: a cardiac arrhythmia risk. (28th March 2012) - Koenig, Xaver; Kovar, Michael; Boehm, Stefan; Sandtner, Walter; Hilber, Karlheinz
ABSTRACT Ibogaine, an alkaloid derived from the African shrub Tabernanthe iboga, has shown promising anti‐addictive properties in animals. Anecdotal evidence suggests that ibogaine is also anti‐addictive in humans. Thus, it alleviates drug craving and impedes relapse of drug use. Although not licensed as therapeutic drug, and despite evidence that ibogaine may disturb the rhythm of the heart, this alkaloid is currently used as an anti‐addiction drug in alternative medicine. Here, we report that therapeutic concentrations of ibogaine reduce currents through human ether‐a‐go‐go‐related gene potassium channels. Thereby, we provide a mechanism by which ibogaine may generate life‐threatening cardiac arrhythmias.